Gelatin hydrogel/contact lens composites as rutin delivery systems for promoting corneal wound healing - Lianghui Zhao; Xia Qi; Tao Cai; Zheng Fan; Hongwei Wang; Xianli Du (Taylor & Francis Group, 2021)
Corneal wound healing is a highly regulated biological process that is of importance for reducing the risk of blinding corneal infections and inflammations. Traditional eye drop was the main approach for promoting corneal wound healing. However, its low bioavailability required a high therapeutic concentration, which can lead to ocular or even systemic side effects. To develop a safe and effective method for treating corneal injury, we fabricated rutin-encapsulated gelatin hydrogel/contact lens composites by dual crosslinking reactions including in situ free radical polymerization and carboxymethyl cellulose/N-hydroxysulfosuccinimide crosslinking. In vitro drug release results evidenced that rutin in the composites could be sustainedly released for up to 14 days. In addition, biocompatibility assay indicated nontoxicity of the composites. Finally, the effect of rutin-encapsulated composites on the healing of the corneal injury in rabbits was investigated. The injury was basically cured in corneas using rutin-encapsulated composites (healing rate, 98.3% ± 0.7%) at 48 h post-operation, while the damage was still present in corneas using the composite (healing rate, 87.0% ± 4.5%). Further proteomics analysis revealed that corneal wound healing may be promoted by the ERK/MAPK and PI3K/AKT signal pathways. These results inform a potential intervention strategy to facilitate corneal wound healing in humans.